Are Families Hard to Reach or Services Difficult to Access? Parent Experiences when a Child is Developmentally Delayed - Cuomo, Belinda Michelle (Curtin University, 2021)
The aim of this thesis was to understand family experiences of noticing and help-seeking for child developmental delays and identify factors that impact pathways to service access. This PhD took a step back from the endpoint of service access and looked instead at the journey leading up to it – acknowledging that experiences during the steps of noticing delays, sharing them with others, and seeking support were vital to how and if parents engaged with early intervention services.